Cooperation Contracts Between Small and Major Scenic Spots in Peak Seasons - Chenchen Yang; Junfeng Dong; Jingjing Hao (SAGE Open, 2019)
This study discusses the cooperation model between the small and major scenic spots in peak seasons of tourism. First, we create a tourism supply chain that contains only one major and one small scenic spots to divert some tourists to a nearby scenic spot, reduce large scenic spot pressure, increase the benefits of small scenic spots, and promote the healthy development of the tourism supply chain. Second, we build two cooperation models between the major and the small scenic spots: the revenue-sharing model and the cost-sharing model. Based on a numerical analysis, we give a more clear comparison about the revenue changes and the overall efficiency changes of the tourism supply chain in these two models. Our results confirm that the cost-sharing model is an ideal cooperation model. In the cost-sharing model, the two parties’ revenues in the tourism supply chain are better than those in the revenue-sharing model, and the entire supply chain efficiency could be improved.